Systematic investigation of failure analysis on a steam trap bypass tube in a coalfired power plant - Mohd Salleh, Mohd Arif Anuar (2007)
A steam trap bypass tube in a power plant was totally fractured. The aim of this study is to examine the evidence presented by the steam trap bypass tube failure, determining the failure mechanism, determining the root cause of the failure and to recommend appropriate corrective actions. The power plant is a coal fired power plant with its normal operation temperature of 540°C. This study consists of failure mode inventory collection of the steam trap bypass tube failure, collection of background information about the process, component function and operating conditions. Detailed investigation carried out by visual examination, nondestructive testing (NDT), metallurgical testing which consists of microstructure examination, chemical testing and mechanical testing. Optical Microscopy (OM), Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-ray Spectroscopy (EDS), Glow Discharge Spectrometer (GDS) and Energy Dispersive X-ray Diffraction (XRD) experiments were used throughout the investigation on the sample obtained. From the evidence with considering the contribution factors such as temperature, pressure and environment, a fault analysis was made and it can be concluded that the cause of failure to the steam trap bypass is due to multi causes which consists of creep failure and hydrogen damage. The root cause of high temperature creep and hydrogen damage which occurred at the steam trap bypass tube is due to material properties that are inadequate for the actual operating conditions of a steam trap bypass tube which is not according to the specification. The material must be actually ASTM SA-335-P22 (2.25Cr-lMo) with 490MPa minimum tensile strength and 320MPa minimum yield strength. However from the investigation found that the material used was ASTM SA-l92 (low strength carbon steel) with 324MPa minimum tensile strength and 180MPa minimum yield strength.